Cartographies of silence: mapping concepts of silence and their contexts - Brown, Melissa Shani (2013)
This study offers a contribution to the discourses surrounding 'silence', arguing that the transformation of the meaning of silence as it shifts between contexts depends upon what it is being defined in opposition to, and that in each case, what is posited in the space marked by silence is of central importance to the discourse surrounding this context. Aware of the interdisciplinary engagements with silence, this thesis presupposes that silence is not 'nothing', and that the question of agency is central to the distinctions between silences. Drawing on a number of theoretical perspectives pertinent to each context, this thesis proceeds by engaging with silence as it is featured in discourses surrounding animals, trauma, secrecy, and listening. These theoretical perspectives are explored also through a number of cultural texts - creative nonfiction, short stories, film, poetry, and also testimony. These case studies are not only illustrative, but also offer further perspectives on each context, and the meaning generated for silence. Unlike most other engagements with silence, this thesis not only takes the definition of silence to be unstable and changeable, but also confronts the question of why 'silence' is used in these discourses, positing that it is its association with space that is being drawn upon across these contexts. This thesis argues that it is because 'silence' comes to be figured as a creator of space, what is at issue in these contexts is what is conceived of as being in this space of silence - Otherness, isolation, individuality, intersubjectivity.